Stereoselective Synthesis of 3-(5-Benzoyl-1-methyl-1H-pyrrol-2-yl)-2-azetidinone Derivatives via an in Situ Generated Ketene - Bananezhad, Behjat; Islami, Mohammad Reza (Synlett, 2017)
A short route toward β-lactams from tolmetin has been developed. In the key step, a ketene was generated on the C-2 of pyrrole ring and reacted with aromatic imines to form trans-β-lactams as the only observed products. The identification of the ketene was confirmed by reaction with the stable free radical TEMPO (TO·).
Keywords: tolmetin; ketenes; electrocyclic reaction; azetidinones; imines